Effect Of Organic Additives On Electrochemi-Cal Processes Influencing Zinc-Air Battery Parameters - Smejkal, Jan (Vysoké učení technické v Brně, Fakulta elektrotechniky a komunikačních technologií, 2020)
This work is focused on the study of influence of selected organic additives on the properties and morphology of zinc deposit on the negative electrode when used in zinc-air accumulators. The deposition was made on the tin plate electrodes in a solutions of 6 mol/l KOH saturated with ZnO with added additives (Abeson Na 50, Flavol KDA, Span 85, Lugalvan G35 and Triton X- 100). All chosen additives were studied with a focus on the morphology of zinc deposit, with regard to their ability to suppress dendritic growth and with focus on zinc corrosion. Changes in zinc morphology were studied by using a Tescan Vega 3 electron microscope and a Rigaku MiniFlex HR 600 X-ray diffractometer.
Keywords: Zinc-air; battery; morphology; dendritic growth; additives